Alcohol confounds relationship between cannabis misuse and psychosis conversion in a high‐risk sample. (9th January 2015) - Auther, A. M.; Cadenhead, K. S.; Carrión, R. E.; Addington, J.; Bearden, C. E.; Cannon, T. D.; McGlashan, T. H.; Perkins, D. O.; Seidman, L.; Tsuang, M.; Walker, E. F.; Woods, S. W.; et al.
<x xml:space="preserve">Abstract</x> Objective Cannabis use has been examined as a predictor of psychosis in clinical high‐risk (CHR) samples, but little is known about the impact of other substances on this relationship. Method Substance use was assessed in a large sample of CHR participants (N = 370, mean age = 18.3) enrolled in the multisite North American Prodrome Longitudinal Study Phase 1 project. Three hundred and forty‐one participants with cannabis use data were divided into groups: No Use (NU, N = 211); Cannabis Use without impairment (CU, N = 63); Cannabis Abuse/Dependence (CA/CD, N = 67). Participants (N = 283) were followed for ≥2 years to determine psychosis conversion. Results Alcohol (45.3%) and cannabis (38.1%) were the most common substances. Cannabis use groups did not differ on baseline attenuated positive symptoms. Seventy‐nine of 283 participants with cannabis and follow‐up data converted to psychosis. Survival analysis revealed significant differences between conversion rates in the CA/CD group compared with the No Use (P = 0.031) and CU group (P = 0.027). CA/CD also significantly predicted psychosis in a regression analysis, but adjusting for alcohol use weakened this relationship. Conclusion The cannabis misuse and psychosis association was confounded by alcohol use. Non‐impairing cannabis use was not related to psychosis. Results highlight the need to control for other substance use, so as to not overstate the cannabis/psychosis connection.